Oxidative Stress and the Severity of Gastroesophageal Reflux Disease: Is There Any Correlation? - Imro'ati, Tri Asih; Sugihartono, Titong; Widodo, Budi; Nefertiti, Eva Pravitasari; Wibawa, I Dewa Nyoman (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Background: Oxidative stress plays a crucial role in the inflammatory response of the oesophageal epithelium; hence, therapies that affect oxidative stress may be a new approach in GERD management.  The objective is to analyze and determine the correlation between Total Oxidant Status (TOS), Total Antioxidant Status (TAS), and Oxidative Stress Index (OSI) with severity of GERD.Methods: This is an observational analytic study using a cross-sectional design,that  conducted at the Endoscopic Unit of three hospitals in Surabaya, which held from June 2020 to March 2021. The 18 to 60 years old subjects who meet the GERD-Q score 8-18 and not meet the exclusion criteria undergo an endoscopic examination to determine the GERD severity and blood test. Data analysis was using the Spearman rank correlation test.Results: This study indicates that most subjects are women, with mean age 39.31±10.99 years, most are GERD grade A, the mean value of TOS, TAS, ISO respectively is 5.18±1.60, 1.58±0.18, and 3.36±1.35. The laboratory test results show insignificant different based on GERD degree.  There is a non-significant positive correlation between TOS and GERD severity, a significant negative correlation  between TAS and  GERD severity, and a significant positive correlation between OSI and GERD severity (respectively, r = 0.121, p = 0.266 vs r = -0.323, p = 0.044 vs r = 0.345, p = 0.033).Conclusion:  The TAS and OSI may be correlated to the GERD severity but still need further investigations.